PENGARUH FOMO DAN KONFORMITAS TEMAN SEBAYA TEHADAP PEMBELIAN IMPULSIF PADA E-COMMERCE TIKTOK DENGAN EMOTIONAL SHOPPING SEBAGAI VARIABEL MEDIASI DALAM PERSPEKTIF BISNIS ISLAM (Studi pada Gen Z pengguna E-commerce Tiktok di Bandar Lampung) - Azalika, Elsa; Muhammad Iqbal; Yeni Susanti (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to find out more about the effect of Fear of Missing Out (FOMO) and peer conformity on impulsive buying in TikTok e-commerce, mediated by emotional shopping. These four variables were tested to draw conclusions. This study uses a quantitative approach, with data collection techniques using questionnaires. The population in this study consists of Gen Z users of TikTok e-commerce in Bandar Lampung. The sampling technique used was purposive sampling, and the number of samples used was 100 respondents, determined using the Slovin formula from a total population of 296,926. The analysis method used in this study was the Structural Equation Modeling (SEM) test, which was processed using Smart-PLS 4. The results of this data testing indicate that FOMO has a significant effect on emotional shopping and impulsive buying, peer conformity has a significant effect on emotional shopping and impulsive buying, emotional shopping significantly affects impulsive buying, and emotional shopping successfully mediates the relationship between FOMO, peer conformity, and impulsive buying